Polyunsaturated fatty acids of marine macroalgae: potential for nutritional and pharmaceutical applications - Pereira, Hugo (2018)
As mammals are unable to synthesize essential polyunsaturated fatty acids (PUFA), these compounds need to be taken in through diet. Nowadays, obtaining essential PUFA in diet is becoming increasingly difficult; therefore this work investigated the suitability of using macroalgae as novel dietary sources of PUFA. Hence, 17 macroalgal species from three different phyla (Chlorophyta, Phaeophyta and Rhodophyta) were analyzed and their fatty acid methyl esters (FAME) profile was assessed. Each phylum presented a characteristic fatty acid signature as evidenced by clustering of PUFA profiles of algae belonging to the same phylum in a Principal Components Analysis. The major PUFA detected in all phyla were C-18 and C-20, namely linoleic, arachidonic and eicosapentaenoic acids. The obtained data showed that rhodophytes and phaeophytes have higher concentrations of PUFA, particularly from the n-3 series, thereby being a better source of these compounds. Moreover, rhodophytes and phaeophytes presented. healthier. Sigma(n-6/)Sigma(n-3) and PUFA/saturated fatty acid ratios than chlorophytes. Ulva was an exception within the Chlorophyta, as it presented high concentrations of n-3 PUFA, alpha-linolenic acid in particular. In conclusion, macroalgae can be considered as a potential source for large-scale production of essential PUFA with wide applications in the nutraceutical and pharmacological industries.